Respuesta :
Answer:
x ≈ 10.58, x ≈ 1.42
Step-by-step explanation:
Given
3(x - 6)² - 26 = 37 ( add 26 to both sides )
3(x - 6)² = 63 ( divide both sides by 3 )
(x - 6)² = 21 ( take the square root of both sides )
x - 6 = ± [tex]\sqrt{21}[/tex] ( add 6 to both sides )
x = 6 ± [tex]\sqrt{21}[/tex] ← exact solutions, or approximate solutions
x = 6 + [tex]\sqrt{21}[/tex] ≈ 10.58 ( to 2 dec. laces )
x = 6 - [tex]\sqrt{21}[/tex] ≈ 1.42 ( to 2 dec. places )
Answers (there's 2):
- [tex]x = 6 - \sqrt{21}[/tex]
- [tex]x = 6 + \sqrt{21}[/tex]
I hope this helps!